2017
DOI: 10.1016/j.msksp.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the methodological quality of controlled clinical trials for myofascial trigger point treatments for the period 1978–2015: A systematic review

Abstract: The average PEDro score of CCTs for MTrP treatments does not reach the cut-off of 6 proposed for moderate to high methodological quality. Nevertheless, a promising trend towards an increase of the average methodological quality of CCTs for MTrPs was recorded. More high-quality CCT studies with thorough research procedures are recommended to enhance methodological quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Dry needling is a commonly applied intervention for MTrPs [11,12,13]; clinically, static stretching is usually performed after dry needling treatment [14,15,16]. More specifically, the dry needling technique focuses on accurate punctures into the MTrPs, while stretching targets the muscles around the MTrPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry needling is a commonly applied intervention for MTrPs [11,12,13]; clinically, static stretching is usually performed after dry needling treatment [14,15,16]. More specifically, the dry needling technique focuses on accurate punctures into the MTrPs, while stretching targets the muscles around the MTrPs.…”
Section: Introductionmentioning
confidence: 99%
“…[21]. A large number of studies have confirmed the beneficial effects of skeletal muscle stretching on muscle performance, range of motion and even neurological responses [13,14,15,16,22,23]. Recently, a study from Austria showed that one minute of static stretching increases H-reflex excitability and decreases muscle spindle sensitivity [16].…”
Section: Introductionmentioning
confidence: 99%
“…An a priori decision was made to only include articles with a PEDro score of 6 or higher. This follows the PEDro recommendations that scores equal to or higher than 6 represent moderate to high methodological quality [25].…”
Section: Methodsmentioning
confidence: 99%
“…The phenomenon under study should be measured by previously validated instruments, the study sample should be of sufficient size to avoid false-negative results, certain statistical tests should be used only if their assumptions were met, and caveats of the study should be clearly and frankly stated, so the readers can draw correct conclusions ( 1 ). However, although the quality criteria for clinical and observational studies are well known and undisputed, they are still not followed completely, as several recent studies have demonstrated ( 2 - 4 ).…”
Section: Introductionmentioning
confidence: 99%